Research on topology optimization design of wind turbine blade webs - FAN Shijie; SHOU Haonan; MIAO Weipao; ZHU Haibo; LI Chun; YUE Minnan (Jixie qiangdu)
ObjectiveStructural optimization of wind turbine blades is one of the most important ways to enhance performance, reduce mass and lower costs. Currently, the research on structural optimization focuses on the blade size or layup scheme, and the overall configuration inside the blade is relatively fixed, but it also limits the structural innovation to a certain extent.MethodsTherefore, Abaqus softwave topology optimization module was adopted to optimize the design of the blade web structure to seek for the optimal material layout, to obtain a new blade structural configuration to achieve the purpose of lightweighting.ResultsThe results show that the mass of the web plate is reduced by about 4.56% after optimization; the optimization of the blade web topology does not affect the overall mass distribution and stiffness distribution of the blade, and maintains good vibration resistance; the maximum stress of the optimized web plate increases, but it does not yet exceed the maximum permissible stress of the material; the flexure factor of each order decreases, which is due to the reduction of the material of the web plate to weaken the role of its support for the surface of the blade, but it still remains in the safe range.